Measuring Malaysian Students Achievement Level in Arabic Morphology: Improving and Developing Curriculum - Yasin Mohamed Yasin M. Sidiq; Hassan Mohamed Doka; Mauidlotun Nisa; Kawakib Elnour Osman (Buletin Al-Turas, 2020)
This study aimed to identify the level of achievement of Malaysian students in Arabic Morphology material on three areas, previous study period, gender, and student education specialization. This research was a field research conducted on Malaysian students studying Arabic, at the International Islamic University Matriculation Center (IIUMC) in Kuala Lumpur-Malaysia. This study concluded that previous study periods, gender, and education specialization had an important role in this identification that became a reference for the improvement of Arabic Morphology learning curriculum. Students who were first learning Arabic in IIUMC had a high success rate only in matching letters (Anita) with pronouns and fi'il al-madi Shahih, and Mahmuz, and pronouns fi'il al-mahi al-Mithal. As for those who have studied Arabic for 5 years, 6 years, and 7 years have a high level of ability also in matching letters (Anita) with the pronouns and fi'il al-madi al-ajwaf. The level of ability of male students was lower than female students in all aspects without exception in matching letters (Anita) with pronouns and verbs that begin with the letter Ta’. As for students specializing in Arabic, Sharia, and Humanities, Reveal Knowledge and the Qur'an, and Arabic had different levels of success in accordance with their specialization, such as students with Arabic specialization had a high level of success in all the discussions that had been mentioned, however, for students with other specialties not. From the findings, there are several suggestions, namely communicative approach, gradualism, adoption of the most frequent morphological positions, introduction of grammar through meaning, reconciliation of teaching methods, designing Morphology materials, and exchanging cognitive programs for teachers and students.